Factors Associated With the Severity of Chronic Constipation Among Japanese University Students - Nhu Thi Hanh Vu; Huong Tu Lam; Shunsuke Miyauchi; Naoki Ishiuchi; Atsuo Yoshino; Yoshie Miyake; Shiro Oka; Yuri Okamoto; Duc Trong Quach; Shinji Tanaka; Toru Hiyama (JGH Open)
ABSTRACT Background and Aim Chronic constipation (CC) is a prevalent gastrointestinal disorder in which individuals with more severe CC significantly decrease their quality of life and often require more active medical intervention. This study aimed to identify the rate and risk factors associated with moderate‐to‐severe CC among Japanese university students. Methods A cross‐sectional study was conducted among university students diagnosed with CC according to the Rome IV criteria at Hiroshima University, Hiroshima, Japan. The online questionnaire collected data on demographics, lifestyle habits, family history of constipation, and psychological assessments via the Beck Depression Inventory, Eating Attitudes Test‐26, and Bulimic Investigatory Test. CC severity was classified based on the Bristol Stool Form Scale (BSFS), spontaneous bowel movements (SBM), and associated symptoms. Multivariate logistic regression analysis was performed to determine independent risk factors. Results Among the 779 CC participants, 47% were classified as having moderate‐to‐severe CC. Independent risk factors associated with moderate‐to‐severe CC included age of CC onset < 18 years (OR: 1.374, 95% CI: 1.017–1.857), female sex (OR: 1.444, 95% CI: 1.058–1.969), family history of CC (OR: 1.449, 95% CI: 1.072–1.958), and sleep duration ≤ 6 h per day (OR: 1.350, 95% CI: 1.011–1.802). Conclusions Moderate‐to‐severe CC was highly common among Japanese students with CC, and risk factors included early onset, female sex, family history of CC, and short sleep duration. These findings suggest that early diagnosis and development of management strategies may be needed to enhance the quality of life and health outcomes of affected individuals.